Practising with Deleuze: Design, Dance, Art, Writing, Philosophy - Attiwill, Suzie; Bird, Terri; Eckersley, Andrea; Pont, Antonia; Roffe, Jon; Rothfield, Philipa (Edinburgh Edinburgh University Press, 2017)
The first systematic reading of Gilles Deleuze's mature philosophy through the lens of creative practiceSix authors two fine artists, a dancer, a creative writer, a designer and a philosopher open multiple dialogues between contemporary creative practices and the generative philosophy of Deleuze. These conversations are focused around key aspects of production: forming, framing, experiencing, encountering and practising.Key FeaturesMaintains a rigorous relationship with Deleuzes texts, including Difference and Repetition and A Thousand PlateausGives creative practitioners a way to engage creatively with the ideas of DeleuzeDemonstrates a creative approach for philosophers to engage conceptually with arts practitionersWith an introduction by Gregory Flaxman
Keywords: Deleuze, Gilles -- 1925-1995; Dance; Fine art; Literature; Philosophy